PERSONAL BEING AT THE BORDER OF NATIONAL CULTURES - Загрійчук, І. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the problems of ambivalence marginality which appears at the border of national cultures are considered as well as the role of awareness of the state of hanging between cultures in the personal being of the individual.